2019
DOI: 10.1037/pspp0000167
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in attachment orientation over a 59-year period.

Abstract: Research on individual differences in attachment-and their links to emotion, cognition, and behavior in close relationships-has proliferated over the last several decades. However, the majority of this research has focused on children and young adults. Little is known about mean-level changes in attachment orientation beyond early life, in part due to a dearth of longitudinal data on attachment across the life span. The current study used a Q-Sort-based measure of attachment to examine mean-level changes in at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 109 publications
4
36
0
3
Order By: Relevance
“…Being familiar with situations and knowing one’s partner and what to expect from them may also prevent insecure individuals to adopt negatively biased perceptions that may perpetuate their insecurities [ 34 ]. Previous research has shown that attachment insecurity decreases with age [ 8 ], which might partly be explained by the fact that partners come to know each other well over time and become experienced with a broad range of situations together, leaving less room for interpersonal noise [ 39 ] and negative interpretations [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being familiar with situations and knowing one’s partner and what to expect from them may also prevent insecure individuals to adopt negatively biased perceptions that may perpetuate their insecurities [ 34 ]. Previous research has shown that attachment insecurity decreases with age [ 8 ], which might partly be explained by the fact that partners come to know each other well over time and become experienced with a broad range of situations together, leaving less room for interpersonal noise [ 39 ] and negative interpretations [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such attachment insecurities are linked to several detrimental outcomes for personal and relational well-being [ 3 , 4 , 5 , 6 ]. Luckily, attachment insecurities are not set in stone; attachment tendencies can vary across partners [ 7 ] and change across the life course [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, our findings suggest that being in a romantic relationship has a moderating effect on the terror from relationships that avoidant men experience. Whereas some research suggests that being in a committed relationship may actually increase the negative association of attachment insecurities and relationship satisfaction and commitment (Hadden, Smith, & Webster, 2014), many findings support the idea that being in a long-term romantic relationship may contribute to positive changes in context-specific and general levels of attachment anxiety and avoidance (e.g., Arriaga et al, 2014;Chopik et al, 2019;Shaver & Mikulincer, 2008). For instance, during the formation of close relationships, sexual desire and intimacy may reduce attachment insecurities (Mizrahi, Hirschberger, Mikulincer, Szepsenwol, & Birnbaum, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, being in a close long-term relationship with a responsive and supportive romantic partner may also lead to contextual and global increases in attachment security (e.g., Arriaga, Kumashiro, Finkel, VanderDrift, & Luchies, 2014;Shaver & Mikulincer, 2008). A recent longitudinal study examining changes in attachment orientation over a 59-year period found that being in a relationship predicted lower levels of anxiety and avoidance across adulthood (Chopik, Edelstein, & Grimm, 2019). Avoidant singles may not be able to benefit from close relationships in the same way as others; for them, close relationships may not serve an anxiety-buffering function, and they may prefer to remain alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of the literature on adult attachment tends to portray individuals as being either chronically anxious or avoidant in their attachment orientations, attachment tendencies can change over time [ 16 ] and individuals can hold multiple different attachment representations [ 17 , 18 , 19 , 20 ]. People can develop different working models and corresponding attachment orientations about others in general, types of relationships such as friendships and romantic relationships in general, and specific others such as a current partner, friend, or parent.…”
Section: Overview Of Attachment Theorymentioning
confidence: 99%